2000
DOI: 10.1086/315708
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Antibiotic‐Resistant Bacterial Mutants: Allelic Diversity among Fluoroquinolone‐Resistant Mutations

Abstract: To obtain a general framework for understanding selection of antibiotic-resistant mutants, allelic diversity was examined with about 600 fluoroquinolone-resistant mutants of mycobacteria. Selection at low fluoroquinolone concentration produced many low-level resistance mutants. Some of these contained mutations that conferred unselected antibiotic resistance; none contained alterations in the quinolone-resistance-determining region of the GyrA protein, the principal drug target. As selection pressure increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 38 publications
(32 reference statements)
11
107
2
Order By: Relevance
“…For example, selection of mutants at different quinolone concentrations -chosen to reflect known concentrations in patientswould test the hypothesis that nfxB mutants are more prevalent at lower drug concentrations. A previous study in Mycobacterium has shown that gyrA mutations are more likely to be selected at high quinolone concentrations, with non-gyrA mutations prevalent at low concentrations (Zhou et al, 2000). However, this study did not identify the nongyrA mutations, and so does not bear directly on the differences in non-gyrase mutations described here.…”
Section: Testing the Hypothesesmentioning
confidence: 58%
See 2 more Smart Citations
“…For example, selection of mutants at different quinolone concentrations -chosen to reflect known concentrations in patientswould test the hypothesis that nfxB mutants are more prevalent at lower drug concentrations. A previous study in Mycobacterium has shown that gyrA mutations are more likely to be selected at high quinolone concentrations, with non-gyrA mutations prevalent at low concentrations (Zhou et al, 2000). However, this study did not identify the nongyrA mutations, and so does not bear directly on the differences in non-gyrase mutations described here.…”
Section: Testing the Hypothesesmentioning
confidence: 58%
“…Drug concentrations can vary dramatically amongst tissues and, as previously noted, different resistance mutations can be selected at different antibiotic concentrations (Zhou et al, 2000). Studies of in vivo ciprofloxacin concentrations in CF patients have found systematically lower drug levels in sputum than in blood (sputum concentrations of 0.2-1.9 mg l 21 versus blood concentrations of 2.4-4 mg l 21 , depending on dose and study; Pedersen et al, 1987, and references therein).…”
Section: Hypothesis 1: Effective Dosementioning
confidence: 95%
See 1 more Smart Citation
“…When drug concentration increases, the fraction of cells that are recovered as colonies decreases, levels to a broad plateau, and then decreases a second time [4,10,11]. The initial decrease arises from the inhibition of wild-type growth and occurs at concentrations approximated by the MIC.…”
Section: Measuring the Mutant Selection Windowmentioning
confidence: 99%
“…The plateau is the result of mutant subpopulations that are present at low frequencies (e.g., 10 Ϫ6 to 10 Ϫ8 ). Colonies that are recovered at low fluoroquinolone concentrations are predominantly caused by nontarget (nongyrase) mutants [10,12,13], whereas at moderate quinolone concentrations, several different gyrA (gyrase) mutants are recovered [10]. When drug concentration increases, only the more protective gyrA mutations are observed; when drug concentration is high enough to block the growth of the least susceptible single-step mutant, colony recovery decreases sharply a second time.…”
Section: Measuring the Mutant Selection Windowmentioning
confidence: 99%